Pengaruh ROE, EPS, OCF, Size, DER, CR dan Growth Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur di Bursa Efek Indonesia (BEI) - Armereo, Crystha; Fitri Rahayu, Pipit (Akuntansi dan Manajemen, 2019)
The objective of this research is to identify the influence of return on equity, earnings per share, operating cash flow, size, debt to equity ratio, current ratio, and growth to dividend payout. Data collected from manufacturing companies that listed on Indonesian Stock Exchange for three years period 2014 to 2016. Sample selected by using purposive sampling method. There are 38 companies meet the criteria and used as sample. The statistical method used in this research is multiple regression. Result of this research showed that return on equity, earnings per share, and growth have influence dividend payout but operating cash flow, size, debt to equity ratio, and current ratio have no influence towards dividend policy.